Co-occurrence analyzis of key concept on risk-taking in organizational management research - Gorzeń-Mitka, Iwona (Management and Administration Journal, 2020)
Risk-taking is a pivotal feature of entrepreneurship and business development. Poor management of business risk often leads to the loss of competitiveness with the consequence of business failure, and in contrast, it improves business sustainability when risks are managed effectively. The aimof thisresearch is to identify leading concepts and trends in research on risk-taking in organizationalmanagement researchby network analysis of keywords co-occurrence. Mapping knowledge domain was used as a useful method in bibliometrics. We analyzed 2912 records from Scopus database to risk-taking in organizational management research with the help of VOSviewer software tool. In particular, keywords co-occurrence analysis to visually explore knowledge bases, topic distribution, research fronts and research trends in the field of risk-taking research in a management context were adopted.